Rancang Bangun Sistem Ujian Online Pada MTs Al-Istiqomah Belinyu - Anggelia, Bela; Andriyanto, Sidhiq; Fujiyanti, Linda (Jurnal Inovasi Teknologi Terapan, 2023)
In the digital era today, information technology is becoming very important in various fields, one of which is in the field of education. In the field of education, information technology can be used to facilitate the learning and teaching process. One of them is by using online examination system. In this research, we tried to design and develop an online examination system at MTs Al-Istiqomah Belinyu. This system was developed using PHP and MySQL as programming language and database, using Codeigniter 4 and Bootstrap 5 as framework. The system has features such as login, online examination, and examination results. In addition, the system also has features to manage student and teacher data, manage examination questions and manage examination results. This system is expected to facilitate the examination process and increase time efficiency for teachers and students. In addition, this system is also expected to improve the quality of the examination and the learning results of students. Examination results obtained from this system can also be used as evaluation material for teachers and schools in improving the quality of education.